2022
DOI: 10.1093/eurheartj/ehac544.2948
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin inhibits increased Na influx in HFpEF cardiomyocytes and reduces arrhythmic activity in human atrial trabeculae

Abstract: Background Heart failure with preserved ejection fraction (HFpEF) is a major health problem associated with substantial morbidity and mortality. However, the underlying pathophysiological mechanisms are poorly understood, and effective treatment strategies are scarce. Importantly, SGLT2i, which have been suggested to improve cellular Na and Ca homeostasis in HFrEF, have recently been shown to also improve clinical outcomes in patients with HFpEF. Interestingly, post-hoc analyses of clinical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Recently, we showed for the first time that intracellular Na + entry and Na + concentration are higher in the atrial myocytes of patients with HFpEF, a condition in which SDB is very common, which could contribute to atrial contractile dysfunction and arrhythmias (Trum et al, 2024). Interestingly, we also showed that patients with SDB have increased late Na + current in their remodeled atria, which could contribute to intracellular Na + overload (Lebek et al, 2022).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Recently, we showed for the first time that intracellular Na + entry and Na + concentration are higher in the atrial myocytes of patients with HFpEF, a condition in which SDB is very common, which could contribute to atrial contractile dysfunction and arrhythmias (Trum et al, 2024). Interestingly, we also showed that patients with SDB have increased late Na + current in their remodeled atria, which could contribute to intracellular Na + overload (Lebek et al, 2022).…”
Section: Discussionmentioning
confidence: 75%
“…Indeed, direct oxidation of the ryanodine type-2 receptors (RyR2) can promote increased diastolic sarcoplasmic reticulum Ca 2+ release and subsequent arrhythmias (Huang et al, 2021). On the other hand, CaMKIIδ is a kinase central to myocardial Na + and Ca 2+ homeostasis that can also be directly oxidized at methionine-281 and -282, thereby releasing the catalytic domain leading to increased enzyme activation (Erickson et al, 2008;Lebek et al, 2023b;Lebek et al, 2024).…”
Section: Sdb-dependent Pathological Mechanisms Promoting Arrhythmiasmentioning
confidence: 99%
See 1 more Smart Citation